An intermediate antipolar phase in NaNbO3 under compression. (18th November 2017) - Kichanov, S. E.; Kozlenko, D. P.; Belozerova, N. M.; Jabarov, S. H.; Mehdiyeva, R. Z.; Lukin, E. V.; Mammadov, A. I.; Liermann, H.-P.; Morgenroth, W.; Dubrovinsky, L. S.; Savenko, B. N.; Raevskii, I. P.; et al.
ABSTRACT: The crystal structure and vibration spectra of sodium niobate NaNbO3 have been studied by means of neutron diffraction, X-ray diffraction and Raman spectroscopy at high pressures. An isostructural phase transformation from the initial antiferroelectric phase to an intermediate antiferroelectric phase HP-I have been observed under 2 GPa. This transformation is caused by complex reorientations of NbO6 octahedra. Subsequent structural phase transition from the phase HP-I to an orthorhombic phase HP-III have been detected at pressures above 10 GPa. This transition leads to suppression of an antiferroelectric state of NaNbO3 . The observed phase transitions are accompanied by anomalies in lattice parameters compression.